Tailoring Cod Gelatin Structure and Physical Properties with Acid and Alkaline Extraction - Svetlana R. Derkach; Yuliya A. Kuchina; Andrey V. Baryshnikov; Daria S. Kolotova; Nikolay G. Voron’ko (Polymers, 2019)
Gelatin (G) was extracted from the skin of Atlantic cod at different pH of the aqueous phase (pH 3, 4, 5, 8 and 9) and at a temperature of 50 ± 1 °C. The yield of gelatin (G3, G4, G5, G8, and G9, respectively) was 49–55% of the dry raw material. The influence of extraction pH on the physicochemical and functional properties of gelatin was studied. Sample G5 was characterized by higher protein content (92.8%) while lower protein content was obtained for sample G3 (86.5%) extracted under more aggressive conditions. Analysis of the molecular weight distribution showed the presence of α- and β-chains as major components; the molecular weight of the samples ranged between 130 and 150 kDa, with sample G5 having the highest molecular weight. IR spectra of all samples had absorption bands characteristic of fish gelatin. The study of the secondary structure demonstrated higher amounts of ordered triple collagen-like helices for G5 extracted under mild conditions. Accordingly, sample G5 formed gels with high values for the storage modulus and gelling and melting temperatures, which decrease as pH changes into acidic or alkaline regions. In addition, the differential scanning calorimetry data showed that G5 had a higher glass transition temperature and melting enthalpy. Thus, cod skin is an excellent source of gelatin with the necessary physicochemical and functional properties, depending on the appropriate choice of aqueous phase pH for the extraction.